Estudo do mecanismo de alagamento e secamento em modelo computacional 2DH baseado em elementos finitos - Siqueira, Jorlaine Machado de (2007)
In this thesis, two mechanisms of wetting and drying are analysed, real and virtual, for regions of narrow tidal creeks rounded for extensive tidal flats, where the behavior of the tidal wave is modified by its interaction which the complex geometry described. A two-dimensional horizontal computational model (2DH), vertically integrated, was used in this investigation. This model is based on the finite elements method. Some simulations show the potentialities of the model on tidal flats subject to wetting and drying, showing good results. The virtual technique of the model was also compared to a numeric experiment, showing a good agreement between the results.